Pemberian Kredit Perbankan dengan Jaminan Hak Cipta - Setiawan, Rayan Reynaldi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The main function of Indonesian banking is as a collector and distributor of funds from the community which aims to support the implementation of national development towards improving the welfare of the people. Article 16 (3) of Copyright Law regulates that Copyright as an intangible movable object can be used as an object of fiduciary security. This means, financial institutions, both bank and non-bank, will accept copyright as a credit collateral. This research aims to see the application of credit provision with copyright guarantees and legal remedies that can be taken to protect banks in case of default on loans filed with copyright guarantees. This research is a normative study using documentary studies. The research was found that Copyright Law implicitly states that copyright is an object of fiduciary security, This regulation as stated in Article 16 paragraph (3) requires a detailed explanation, because it relates to a guarantee at the bank itself to produce a refund process from the debtor to the creditor.